PENGARUH LATIHAN TENDANGAN MAWASHI GERI DENGAN BEBAN TERHADAP KECEPATAN TENDANGAN MAWASHI GERI PADA ATLET KUMITE KARATE JUNIOR PUTRA TAKO PEKANBARU - Stanislaus Pedro Sitohang Z; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that there is still a lack of kick speed when carrying out an attack, especially when the athlete who takes the kick attack at the same time the athlete misses the point and it does not produce results. The purpose of this research was to determine the effect of the training of the mawashi geri kick with the load on the kick speed of the mawashi geri in the junior male kumite karate athletes of tako Pekanbaru. This research will be conducted at dojo tako pekanbaru, Jl.pattimura No.9, Cinta Raja, Sail, Pekanbaru. This research was conducted from November to November 2020. The population which was also the sample in this research were all of the Karate Tako Pekanbaru athletes, totaling 8 people. Based on the results of the pree test and post test data analysis, there are different numbers that increase. After taking the pre-test, the researcher gave a method to increase the kick speed of mawashi geri for 13 meetings with the training method of mawashi geri kicks with weights. Finally, the researcher took a posttest from the mawashi geri exercise that had been given lectures for 13 times with the karate kick speed test, and got Lhitung 0.220 and Ltabel 0.285 data with normal distribution.Key Words: Effect of Kick Training, Kick speed